ZONASI KOMPLIKASI PENYAKIT DIABETES DI WIAYAH BENCANA GUNUNG BERAPI Studi Kasus di Puskesmas Cangkringan - Susanto, Nugroho (Jurnal Formil (Forum Ilmiah) Kesmas Respati, 2018)
Background: Volcanic disasters cause health problems for surrounding communities. Diabetes prevalence is high in advanced populations. Problems that often occur in times such as diabetes that relate to other people during a disaster become a special problem. Previous studies that knew low diabetes, accompanied by increasing diabetes at this price. In disaster areas, diabetics show an emergency condition. The purpose of the study was to look at diabetes suffered and complicating factors in Cangkringan sub-district.Method: Research design with cross sectional. The study population was diabetics in the work area of Cangkringan health center. Samples were estimated 118 samples. Data were collected with medical record documents and taking ordinate points and interviews. Analysis using two approaches univariate and bivariate analysis. Univariate analysis was carried out by analyzing geographic mapping using software epi info version 7. Bivariate analysis with chi square test with 10% CI.Results: Argomulyo is the region with the most diabetes. Vulcano occur in the form of displacement in the form of displacement in the radius of impacted of the volcano. Variables as village impacted, the availability of doctor services significantly influences of DM complications in Cangkringan District. Based on gender, education and age there was no significant effect on the incidence of DM complications at the level of confidence Î± = 0.10. variable age, suffered, regularity of treatment there was no significant relationship between the duration of suffering with complications of diabetes p => 0.05. Based on family history, there was a significant relationship between family history and complications of diabetes p = 0.024.Conclusion: Based on the results and discussion could be concluded 1). Most of the sufferers were displaced after the volcanic eruption in 2010 in people with diabetes and stroke. 2).The biggest data on Diabetes is in Argomulyo due to displacement of residence from a location near the volcano. 4). History of diabetes is the most influential factor for diabetes complications.Key word: Geographic, diabetic, disaster